2021
DOI: 10.3390/cancers13153694
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up of Cured HCV Patients under Real-World Interferon-Free Therapy

Abstract: (1) Background: Treatment of hepatitis C virus (HCV) infections with direct-acting antivirals (DAA) has demonstrated high efficacy and an excellent safety profile. The cured patients showed a sustained virological response and improved liver function, but also a continued risk of hepatocellular carcinoma (HCC) during the 2–3 years of follow-up after treatment; (2) Methods: A total of 192 patients out of 209 of the primary AMBER study were analyzed five years after treatment with ombitasvir/paritaprevir/ritonav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Other studies have also shown the potential for long-term durability of SVR and positive benefits on clinical outcomes for patients who maintain SVR. [26][27][28] Furthermore, in the current study, three of the four enroled participants who experienced virologic failure in a prior study achieved SVR12 after re-treatment; these data support other studies that have shown successful re-treatment of patients who did not achieve SVR after treatment with GLE/PIB. 29 Previous studies on the persistence of resistance-associated substitutions in NS3 have focused on substitutions emerging in DAA-naïve patients treated with NS3-inhibitor-containing regimens.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Other studies have also shown the potential for long-term durability of SVR and positive benefits on clinical outcomes for patients who maintain SVR. [26][27][28] Furthermore, in the current study, three of the four enroled participants who experienced virologic failure in a prior study achieved SVR12 after re-treatment; these data support other studies that have shown successful re-treatment of patients who did not achieve SVR after treatment with GLE/PIB. 29 Previous studies on the persistence of resistance-associated substitutions in NS3 have focused on substitutions emerging in DAA-naïve patients treated with NS3-inhibitor-containing regimens.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest high durability of SVR. Other studies have also shown the potential for long‐term durability of SVR and positive benefits on clinical outcomes for patients who maintain SVR 26‐28 . Furthermore, in the current study, three of the four enroled participants who experienced virologic failure in a prior study achieved SVR12 after re‐treatment; these data support other studies that have shown successful re‐treatment of patients who did not achieve SVR after treatment with GLE/PIB 29…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Hepatitis C virus (HCV) infection, affecting, by the most recent estimations of the World Health Organization (WHO), approximately 71 million people globally, is one of the major public health issues [1,2]. Effective antiviral treatment is a first step to prevent the most serious complications of chronic hepatitis C (CHC), such as liver cirrhosis and hepatocellular carcinoma, resulting in nearly 400,000 deaths annually [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in the commencement of research worldwide on the incidence of HCV infections and on the possibilities of its complete elimination as a public health problem [ 1 , 2 , 3 ]. Although new therapeutic regimens have eliminated the waiting lists for the treatment of diagnosed patients, a large group of patients with HCV remained undiagnosed and at risk of developing cirrhosis and/or hepatocellular carcinoma [ 3 , 4 ]. In 2016, the WHO announced a plan to eliminate viral hepatitis as a public health threat by 2030 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%